PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN IPA UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS IV SDN JATINEGARA 03 PAGI JAKARTA TIMUR - Ramadhani, Sulistyani Puteri; Sarthika, Nilam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of science and technology in the 21st century demands the world of education to continue to innovate in improving the quality of learning. However, based on the results of PISA 2012, the literacy and higher-order thinking skills of Indonesian students are still relatively low. The problem of science learning is still dominated by the use of textbooks and worksheets, and minimal experimental practice, so that students are less active and have difficulty understanding abstract concepts such as photosynthesis. This study aims to develop science learning video media on photosynthesis material to improve the critical thinking skills of fourth-grade students. The study used the ADDIE research and development method. Effectiveness tests through small groups and large groups showed normalized gain values ​​of 0.63 and 0.57, respectively, with a moderate category. These results indicate that learning video media is effective in improving science learning outcomes on photosynthesis material. Thus, learning video media can be an alternative learning innovation that is effective and relevant to the needs of 21st-century education.